2005
DOI: 10.1073/pnas.0502208102
|View full text |Cite
|
Sign up to set email alerts
|

DNA-based vaccines activate innate and adaptive antitumor immunity by engaging the NKG2D receptor

Abstract: The interaction of NKG2D, a stimulatory receptor expressed on natural killer (NK) cells and activated CD8 ؉ T cells, and its ligands mediates stimulatory and costimulatory signals to these cells. Here, we demonstrate that DNA-based vaccines, encoding syngeneic or allogeneic NKG2D ligands together with tumor antigens such as survivin or carcinoembryonic antigen, markedly activate both innate and adaptive antitumor immunity. Such vaccines result in highly effective, NK؊ and CD8 ؉ T cell-mediated protection again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 46 publications
1
28
0
1
Order By: Relevance
“…Accordingly, Andreas Diefenbach et al (23) demonstrated the efficacy of using NKG2D ligands as components of vaccine, which may offer new approaches for malignancies. Moreover, it was shown that DNA-based vaccines encoding syngeneic or allogeneic NKG2D ligands together with tumor antigens could markedly activate both innate and adaptive anti-tumor immunity (24,25 …”
Section: Ul16-binding Proteins (Ulbpsmentioning
confidence: 99%
“…Accordingly, Andreas Diefenbach et al (23) demonstrated the efficacy of using NKG2D ligands as components of vaccine, which may offer new approaches for malignancies. Moreover, it was shown that DNA-based vaccines encoding syngeneic or allogeneic NKG2D ligands together with tumor antigens could markedly activate both innate and adaptive anti-tumor immunity (24,25 …”
Section: Ul16-binding Proteins (Ulbpsmentioning
confidence: 99%
“…6,29,40,41 They were cultured in RPMI-1640 medium supplemented with 10% FBS and 100 μg/ ml amikacin at 37°C with 5% CO 2 atmosphere. The culture medium was replaced with fresh medium every 2-3 d.…”
Section: Cells and Culturesmentioning
confidence: 99%
“…3 By contrast, survivin is prominently overexpressed in most malignant tumors, especially in colon cancer, such as SW480, HCT116 and CT26 and so on. [4][5][6][7] Furthermore, overexpression of survivin frequently correlated with resistance against cancer therapy-induced apoptosis, unfavorable prognosis and abbreviated overall survival. 8 Obviously, the distribution and expression of survivin in vivo has made it a promising target for cancer therapy, 1,9 since downregulation of survivin expression in tumors induces apoptosis and inhibits tumor growth with little toxicity to normal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…NKG2D ligand expression and peptide presentation was targeted to antigen-presenting cells by DNA-based vaccination, as mice received plasmids containing the sequences for NKG2D ligand, H60 and tumor antigen peptides orally. In two distinct colon carcinoma models, this type of vaccination effectively inhibited tumor growth [25]. The vaccination elicited an effective specific T cell response and enhanced NK cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the same line, this work demonstrated that tumor lines expressing NKG2D ligand evoke a strong CD8 + memory response towards the specific cell lines. Notably, the group of Reisfeld recently demonstrated the potential of NKG2D ligands to enhance specific T cell responses [25]. NKG2D ligand expression and peptide presentation was targeted to antigen-presenting cells by DNA-based vaccination, as mice received plasmids containing the sequences for NKG2D ligand, H60 and tumor antigen peptides orally.…”
Section: Discussionmentioning
confidence: 99%